Non-Radiative Processes in Crystals and in Nanocrystals. (1st January 2016) - Collins, J.
Abstract : This paper discusses non-radiative processes that are relevant to the luminescence characteristics of optically active ions doped into insulators or large-gap semiconductors, with particular attention to how these processes are affected as the particle size is reduced from bulk single crystals to as small as a few nanometers. The non-radiative processes discussed in this article are thermal line broadening and thermal line shifting, relaxation via phonons between excited electronic states, vibronic emission and absorption, and phonon-assisted energy transfer. Given that one of the main effects of confinement in these particles is on the phonon density of states, we pay particular attention to how these non-radiative processes are altered due to the change in the phonon density of states as particle size decreases.